Global Value Chain and its implication on Labour: A Case Study on Indian e-tail Market - Jamdade, Sachin Balaji (H. : ĐHKT, 2020)
Global value chain involves splitting up of the production by tasks such as design, marketing, manufacturing and branding. Indian economy has witnessed consumption-driven growth. The role of online retail firms is significant in development. However, the transnational online firms have outperformed the national rivals. Global value chain consists of an independent firm with contracted distribution. It has developed through highly uneven power relations and disintegration of ownership. The relative numbers of buyers and sellers in a segmented market that shape relative bargaining power within the value chain. The e-tail market constitutes most of the informal workforce. The focus of the study is on the social upgrading of workers which includes measures like employment and wages, measurable standards and enabling rights; while on the economic upgrading it looks on the product, process, and functional chains. The research has to find out the vertical and horizontal relations of labour indicators within the global value chain. Also, the manner in which global value chain governs, shapes further wages, skill, training and employment relations in the labour market. The paper discusses the working conditions of labour in the e-tail market in the Indian economy. The research methodology is to be used as a qualitative one, encompassing secondary review and key informant interviews with online retail workers. A structured questionnaire including some close-ended and open-ended questions based on the objective is to be used purposively for collecting primary information from the e-tail market.